2016
DOI: 10.1007/s10103-016-1883-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of diode laser and plasmakinetic in transurethral enucleation of the prostate for treating large volume benign prostatic hyperplasia: a randomized clinical trial with 12-month follow-up

Abstract: The objective of this study is to compare the efficacy and safety of diode laser enucleation of the prostate (DiLEP) with plasmakinetic enucleation of the prostate (PKEP) for symptomatic benign prostatic hyperplasia (BPH) patients with large prostate (volume > 80 ml). From January 2013 to June 2014, 80 consecutive patients were randomized treated with DiLEP (n = 40) or PKEP (n = 40). Perioperative and postoperative outcome data were assessed during a 1-year follow-up. There were no significant preoperative dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…In the RCT performed by Wu et al (), the occurrence rate between DiLEP and BipoLEP was not statistically significant with respect to retrograde ejaculation (30.0% vs. 15.0%, p = .11). Zou et al () also reported a similar incidence of retrograde ejaculation between DiLEP and BipoLEP (45.6% vs. 33.3%, p = .180).…”
Section: Evidence Synthesismentioning
confidence: 84%
“…In the RCT performed by Wu et al (), the occurrence rate between DiLEP and BipoLEP was not statistically significant with respect to retrograde ejaculation (30.0% vs. 15.0%, p = .11). Zou et al () also reported a similar incidence of retrograde ejaculation between DiLEP and BipoLEP (45.6% vs. 33.3%, p = .180).…”
Section: Evidence Synthesismentioning
confidence: 84%
“…One RCT comparing the 12‐month clinical outcome of ThuLEP versus BipolEP revealed an equal improvement in IPSS, QoL, Qmax and PVR, while ThuLEP was associated with less risk of haemorrhage and shorter catheter time, although the difference was of little clinical relevance (Feng, Zhang, Tian, & Song, 2016). There have been three RCT comparing the efficacy of DiLEP versus BipolEP, all revealed equal efficacy in IPSS, Qmax, PVR and QoL at 12 months (Wu et al., 2016; Xu et al., 2013; Zou et al., 2018), while two studies demonstrated that DiLEP was associated with less bleeding and shorter catheter time (Wu et al., 2016; Xu et al., 2013), but the other showed no difference in these perioperative parameters (Zou et al., 2018). Taken together, currently available evidences consistently demonstrated all these energy devices (holmium, thulium, diode and bipolar) achieved equivalent improvements in IPSS, Qmax, PVR and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…DiLEP is advantageous in that it provides markedly reduced blood loss, reduced hospital stay, and decreased catheter indwelling time. 21,22…”
Section: Discussionmentioning
confidence: 99%